O01.5 Origin and predictors of early repeat infections among hiv negative women with trichomonas vaginalis receiving a 2 g dose of metronidazole. (8th July 2017) - Kissinger, Patricia; Muzny, Christina; Mena, Leandro; Lillis, Rebecca; Schwebke, Jane; Beauchamps, Laura; Taylor, Stephanie N; Schmidt, Norine; Ostrenga, Lauren; Secor, W Evan; Martin, David H
Abstract : Introduction: A recent meta-analysis demonstrated superiority of multi-dose metronidazole (MTZ) over the CDC and WHO recommended 2 g dose for the treatment of T. vaginalis (TV). Another study among HIV+ women with TV found higher test-of-cure (TOC)+ rates among women who had asymptomatic bacterial vaginosis (BV) than those without BV. The purpose of this study was to measure the TOC TV+ rate and to examine if the presence of BV influenced that rate. Methods: HIV-/TV+ women treated with 2 g oral directly observed MTZ and who completed their TOC visit 3–12 weeks post treatment were included. Women were tested for TV using NAAT and surveyed via computer at baseline and TOC. Nugent scores≥7, calculated from vaginal gram stain, were considered BV+. MTZ susceptibility testing was performed on TOC TV+ specimens. Results: Of 227 TV+ women included baseline the mean age was 31.3 (S.D. 9.9), 95.2% were African American, 39.3% had multiple male partners in the prior 3 months, 32.3% regularly smoked, 19.4% were binge drinkers, 48.9% had BV and 5.4% had yeast on the gram stain. At TOC, 19.8% were NAAT TV+. Of the 45 TOC-TV+ women, 44 provided sexual exposure information and 10/44 (24.4%) reported sexual re-exposure to baseline partner or sexual exposure to a new partner. Two of 26 (7.7%) TOC+ specimens that underwent susceptibility testing had low to moderate MTZ resistance (50–100 ug/ml). There were no differences in TOC NAAT+ rates by BV, sexual re-exposure to a baseline partner, sexual exposure to a new partner, regular smoking, binge drinking, or by the presence of yeast (p>0.22). Conclusion: TOC NAAT+ rate after 2 g MTZ dose was high (19.8%) and isolates from these women were susceptible to MTZ (94.3%). Most TOC+ women (75.6%) reported no sexual exposure/re-exposure during follow-up suggesting that most cases were treatment failures. Selected behavioural factors and BV did not did not appear to influence TV treatment. The 2 g MTZ dose for TV recommended by CDC and WHO, should be reevaluated in light of more sensitive NAAT.